Facilitating ambidexterity with HR practices – a case study of an automotive supplier. (1st January 2013) - Renzl, Birgit; Rost, Martin; Kaschube, Jürgen
In dynamic environments organisations are challenged to simultaneously explore new capabilities and to exploit existing ones; a capability that has been named 'ambidexterity'. Research identified that ambidexterity can be achieved through different means (e.g., structural ambidexterity, contextual ambidexterity). Ambidexterity, however, is always based on individual competencies of organisational members. Yet, the link between organisational means aimed at achieving ambidexterity and the individual competencies of the employees have remained imprecise. In order to tackle this link, we conducted a case study at a technological leader in the automotive supplier industry. We analyse how ambidexterity can be combined with issues of psychological management research, transformational leadership style, competency management and new theories on work performance. Thereby, we shed light on the link between individual competencies and human resource (HR) practices aimed at achieving organisational ambidexterity. Our research allows inferring recommendations for academics and practitioners how to better manage ambidexterity.